High-Q2 neutral current cross sections in e+ p deep inelastic scattering at √s = 318 GeV - Chekanov, S; Derrick, M; Krakauer, D; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; et al. (2004)
Cross sections for e+ p neutral current deep inelastic scattering have been measured at a center-of-mass energy of √s = 318 GeV with the ZEUS detector at HERA using an integrated luminosity of 63.2 pb -1. The double-differential cross section, d2σ/ dxdQ2, is presented for 200 GeV2 < Q2 < 30 000 GeV2 and for 0.005 < x < 0.65. The single-differential cross sections dσ/dQ2, dσ/dx and dσ/dy are presented for Q2 > 200 GeV2. The effect of Z-boson-exchange is seen in dσ/dx measured for Q2 > 10 000 GeV2. The data presented here were combined with ZEUS e+ p neutral current data taken at √s = 300 GeV and the structure function F2em was extracted. All results agree well with the predictions of the Standard Model.